17O-excess in tropical cyclones reflects local rain re-evaporation more than moisture source conditions - Sun, Chijun (2024)
17O-excess is a relatively new water isotope parameter that could potentially provide useful information about the hydrological cycle. Previous works focusing on 17O-excess in polar regions suggest that it primarily tracks moisture source relative humidity, but little is known about how to interpret 17O-excess data in lower latitudes. Here we present quasi-hourly triple oxygen isotope data of precipitation collected from two tropical cyclones in Texas and Louisiana in 2020 to understand the impacts of environmental and meteorological processes on the 17O-excess of low-to mid-latitude precipitation. We find that at both hourly timescales and the event scale, 17O-excess is strongly correlated to changes in on-site rainfall intensity and relative humidity, which is consistent with the theory that the isotopic fractionation associated with rain re-evaporation lowers the 17O-excess of the remaining droplet. In addition, although evaporative conditions at the moisture source region may also influence 17O-excess of water vapor transported to the precipitation site, their impacts are likely overprinted by the post-condensation rain re-evaporation processes. Our results thus suggest that 17O-excess can be used as a proxy for local rather than source region evaporative conditions during tropical cyclones.